2015
DOI: 10.1093/jnci/dju424
|View full text |Cite
|
Sign up to set email alerts
|

Palliative Care and the Aggressiveness of End-of-Life Care in Patients With Advanced Pancreatic Cancer

Abstract: PC consultation and a higher intensity of PC were associated with less aggressive care near death in patients with advanced pancreatic cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
108
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(123 citation statements)
references
References 45 publications
12
108
3
Order By: Relevance
“…For instance, women had lower odds of hospitalization and receipt of aggressive care in several EOL care studies, whereas individuals who reported a black race/ethnicity, a lower SES, and comorbidities had higher odds. [28][29][30][31][32] Our finding that increased age was associated with lower rehospitalization rates was consistent with results of a Canadian study on EOL care for advanced pancreatic cancer 33 and a US study of Medicare beneficiaries with poor-prognosis cancers in the last 6 months of life. 28 However, this finding was inconsistent with one study, in which increased age was associated with more aggressive EOL care.…”
Section: Discussionsupporting
confidence: 80%
“…For instance, women had lower odds of hospitalization and receipt of aggressive care in several EOL care studies, whereas individuals who reported a black race/ethnicity, a lower SES, and comorbidities had higher odds. [28][29][30][31][32] Our finding that increased age was associated with lower rehospitalization rates was consistent with results of a Canadian study on EOL care for advanced pancreatic cancer 33 and a US study of Medicare beneficiaries with poor-prognosis cancers in the last 6 months of life. 28 However, this finding was inconsistent with one study, in which increased age was associated with more aggressive EOL care.…”
Section: Discussionsupporting
confidence: 80%
“…39 Palliative care consultations for patients with advanced cancer have also been shown to reduce the quantity and intensity of life-prolonging care received toward the EOL. [40][41][42][43][44] Conversely, the lack of palliative care team consultation has been shown to be a predisposing factor for futile life-sustaining treatments at EOL. 45 An observational study suggested that inpatient palliative care led to fewer or no transitions in care settings at EOL.…”
Section: Eol Care In Oncologymentioning
confidence: 99%
“…These services have been associated with a reduced need for EOL emergency department visits, reduced length and frequency of hospitalization, and fewer intensive care unit (ICU) admissions and in-hospital deaths. [40][41][42][43][44] Palliative care has been shown to reduce symptom burden, improve QOL, and increase the odds of dying at home. Similarly, a 2013 Cochrane Database systematic review that analyzed home palliative care in patients with advanced illness demonstrated a reliable reduction of symptom burden and an increased likelihood of dying at home without a negative impact on caregiver grief.…”
Section: Eol Care In Oncologymentioning
confidence: 99%
“…[6][7][8][9][10][14][15][16]22 Definitions of the financial terms are given in the Appendix (online only). The Johns Hopkins Institutional Review Board approved this study.…”
mentioning
confidence: 99%